The Impact of Nano- and Micro-Silica on the Setting Time and Microhardness of Conventional Glass-Ionomer Cements - Zeynep A. Güçlü; Şaban Patat; Nichola J. Coleman (MDPI AG, 2024)
The objective of this study was to investigate the effect of the incorporation of 2, 4 or 6 wt% of amorphous nano- or micro-silica (Aerosil® OX 50 or Aeroperl® 300 Pharma (Evonik Operations GmbH, Essen, Germany), respectively) on the net setting time and microhardness of Ketac™ Molar (3M ESPE, St. Paul, MN, USA) and Fuji IX GP® (GC Corporation, Tokyo, Japan) glass-ionomer cements (GICs) (viz. KM and FIX, respectively). Both silica particles were found to cause a non-linear, dose-dependent reduction in setting time that was within the clinically acceptable limits specified in the relevant international standard (ISO 9917-1:2007). The microhardness of KM was statistically unaffected by blending with 2 or 4 wt% nano-silica at all times, whereas 6 wt% addition decreased and increased the surface hardness at 1 and 21 days, respectively. The incorporation of 4 or 6 wt% nano-silica significantly improved the microhardness of FIX at 1, 14 and 21 days, with no change in this property noted for 2 wt% addition. Micro-silica also tended to enhance the microhardness of FIX, at all concentrations and times, to an extent that became statistically significant for all dosages at 21 days. Conversely, 4 and 6 wt% additions of micro-silica markedly decreased the initial 1-day microhardness of KM, and the 21-day sample blended at 4 wt% was the only specimen that demonstrated a significant increase in this property. Scanning electron microscopy indicated that the nano- and micro-silica particles were well distributed throughout the composite structures of both GICs with no evidence of aggregation or zoning. The specific mechanisms of the interaction of inorganic nanoparticles with the constituents of GICs require further understanding, and a lack of international standardization of the determination of microhardness is problematic in this respect.